The Effect of the Agreement between the Saudi Railway Company (SAR) and MEDLOG Company on the Quality of Logistics Services between Dammam and Riyadh (المجلة الدولية للبحوث العلمية, 2024)
The current study aims to identify the extent to which the agreement between the Saudi Railways and MEDLOG Company affected the quality of logistics operations between Dammam and Riyadh, determine the challenges and problems facing the conclusion of the agreement, explore the extent to which customers and partners satisfied with the agreement, and suggesting future expectations for concluding an agreement between the Saudi Railway Station and Madlouk Company.  The researcher employed the descriptive method. The study population consisted of interested individuals, therefore, an electronic link was distributed, and the sample included (97) individuals from the study population. A questionnaire was used to collect the responses from the study sample. The agreement between the Saudi Railway Station and MEDLOG Company has increased the quality of logistics operations between Dammam and Riyadh greatly by increasing the volume of shipments transported between the two cities, reducing costs, improving delivery time, and raising the efficiency of operations in general. The researcher recommended concluding strategic partnerships with other companies in various sectors, such as industry and trade to enhance supply chains.